Demographic Characteristics and Ocular Biometrics of Cataract Surgery Patients at KMU Eye Clinic Lamongan in April 2024 - Salsabila, Khansa Dhea; Unari, Uyik (Oftalmologi : Jurnal Kesehatan Mata Indonesia, 2025)
ABSTRACT Introduction: Cataract remains the leading cause of blindness in Indonesia, accounting for over 80% of severe visual impairment. Given the substantial burden in East Java, this study aimed to characterize cataract patients' demographic and ocular biometric profiles at KMU Eye Clinic Lamongan. Methods: A cross-sectional descriptive study reviewed the medical records of patients who underwent cataract surgery in April 2024. Inclusion criteria included patients scheduled for surgery via phacoemulsification or Small Incision Cataract Surgery (SICS). Data collected included demographics, systemic comorbidities, and ocular biometric parameters: intraocular pressure (IOP), anterior chamber depth (ACD), lens thickness (LT), intraocular lens (IOL) power, and surgery duration. Result: A total of 192 patients were analyzed. The mean age was 63.6±8.3 years, with 50% aged 60-69 years. Hypertension (66.7%) and diabetes (17.2%) were the most common systemic comorbidities. Severe visual impairment (≤3/60) was observed in 59.9% of cases. Phacoemulsification was performed in 97% of surgeries. Mean values for ocular biometrics were: IOP 15.1±3.6 mmHg, ACD 3.2±0.4 mm, LT 4.3±0.7 mm, IOL power 19.8±4.1 D, and surgery time 9.5±3.5 minutes. Conclusion: Most cataract patients at KMU Eye Clinic Lamongan were elderly with significant systemic comorbidities and severe visual impairment. Phacoemulsification was the preferred surgical technique. Ocular biometric analysis provided essential information for preoperative planning and optimizing cataract management.